Halal Logistic Business Model Development in Indonesia - Yuliani Dwi Lestari; Liane Okdinawati; Togar Simatupang (International Journal of Supply Chain Management, 2018)
As the study on halal logistic has been gaining recognition, this study aims to develop the business model for the halal logistic in Indonesia. With the biggest number of Muslim population, the shifting toward to halal logistic becomes critical in keeping the business sustainability. Adopting the VIP framework, this study defines a business model through an elaboration of primary and secondary data. Primary data is derived from an in-depth interview with three industries representing agribusiness, retail, and logistic provider; while secondary data is derived from a comprehensive literature review to discover the halal logistic business model development. Through an extensive analysis, value exchange (V), information exchange (I), and business process (P) are presented as the basis to construct a business model of halal logistic in Indonesia.